Female beauty in British literature: diachronic aspect - Wei, Liyushan (Київський національний університет імені Тараса Шевченка, 2026)
This paper analyzes the concept of "concept" in language and the concept of female beauty from a linguistic perspective, exploring the diachronic evolution of female beauty in British literature and its socio-cultural significance. In comparison with the original draft, the formulation has been kept close to the initial wording, but the linguistic focus has been made more precise: the paper studies female beauty as a concept that is verbalised through lexical, stylistic, syntactic, pragmatic and conceptual means. Based primarily on representative literary works such as Jane Eyre from the Victorian era, Mrs. Dalloway from the modernist period, and Girl, Woman, Other from the contemporary period, the paper conducts a diachronic analysis of the physical appearance, inner world and self-awareness of female characters across different historical periods. The analysis is supplemented with the data-collection files provided for Mrs. Dalloway and Girl, Woman, Other, which group the examples according to linguistic level, character, quotation, function and diachronic note. From a linguistic perspective, this paper mainly analyzes female images through vocabulary, figurative devices and sentence structure, while also paying attention to who evaluates beauty and how beauty is conceptually redefined. The evolution of female beauty from submissiveness and purity to female subjectivity, diversity and self-definition reflects the changing societal perception of female value in British literature. This study illustrates the close connection between language, culture, literature and society.

У цій статті аналізується поняття «концепт» у мові та поняття жіночої краси з лінгвістичної точки зору, досліджуючи діахронічну еволюцію жіночої краси в британській літературі та її соціально-культурне значення. Порівняно з початковим варіантом, формулювання збережено близьким до початкового, але лінгвістичний фокус уточнено: у статті досліджується жіноча краса як поняття, яке вербалізується за допомогою лексичних, стилістичних, синтаксичних, прагматичних та концептуальних засобів. Спираючись переважно на репрезентативні літературні твори, такі як «Джейн Ейр» вікторіанської епохи, «Місіс Делловей» модерністського періоду та «Дівчина, жінка, інша» сучасного періоду, у статті проводиться діахронний аналіз зовнішності, внутрішнього світу та самосвідомості жіночих персонажів у різні історичні періоди. Аналіз доповнюється файлами збору даних, наданими для «Місіс Делловей» та «Дівчина, жінка, інша», які групують приклади за лінгвістичним рівнем, персонажем, цитатою, функцією та діахронічною нотою. З лінгвістичної точки зору, ця стаття переважно аналізує жіночі образи через лексику, образні засоби та структуру речень, а також звертає увагу на те, хто оцінює красу та як краса концептуально переосмислюється. Еволюція жіночої краси від покірності та чистоти до жіночої суб'єктивності, різноманітності та самовизначення відображає зміну суспільного сприйняття жіночої цінності в британській літературі. Це дослідження ілюструє тісний зв'язок між мовою, культурою, літературою та суспільством.
Keywords: concept; concept of female beauty; linguistic representation; lexical verbalisation; British literature; diachrony; feminism; концепція; концепція жіночої краси; лінгвістична репрезентація; лексична вербалізація; британська література; діахронія; фемінізм